Tuneable paramagnetic susceptibility and exciton g-factor in Mn-doped PbS colloidal nanocrystals - Turyanska, L.; Hill, R.J.A.; Makarovsky, Oleg; Moro, F.; Knott, A.N.; Larkin, O.J.; Patanè, Amalia; Meaney, A.; Christianen, P.C.M.; Fay, M.W.; Curry, R.J. (Royal Society of Chemistry, 2014)
We report on PbS colloidal nanocrystals that combine within one structure solubility in physiological solvents with near-infrared photoluminescence, and magnetic and optical properties tuneable by the controlled incorporation of magnetic impurities (Mn). We use high magnetic fields (B up to 30 T) to measure the magnetization of the nanocrystals in liquid and the strength of the sp-d exchange interaction between the exciton and the Mn-ions. With increasing Mn-content from 0.1% to 7%, the mass magnetic susceptibility increases at a rate of ~ 10-7 m3/kg per Mn percentage; correspondingly, the exciton g-factor decreases from 0.47 to 0.10. The controlled modification of the paramagnetism, fluorescence and exciton g-factor of the nanocrystals is relevant to the implementation of these paramagnetic semiconductor nanocrystals in quantum technologies ranging from quantum information to magnetic resonance imaging.